Faktor risiko dan pencegahan dermatitis kontak akibat kerja: Literature review - Mutiara, Mutiara; Nurelly, Nurelly; Nurdin, Abbas Zavey; Adharia, Adharia; Setiawati, Solecha (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Occupational contact dermatitis (OCD) is a significant occupational health problem, particularly among industrial workers who are routinely exposed to chemicals and irritants. Risk factors are multifactorial, including occupational factors (duration and frequency of chemical exposure, wet work), individual factors (age, gender, history of atopy, personal hygiene), and work environment factors (temperature, humidity, availability of sanitation facilities, and use of PPE). Effective prevention includes exposure control, appropriate use of PPE, worker education and training, and improving the work environment to maintain skin integrity and reduce the incidence of OCD. Purpose: To identify risk factors and prevention of occupational contact dermatitis. Method: This study used a systematic literature review method, searching PubMed, ScienceDirect, Scopus, Google Scholar, and ProQuest for articles published between 2020 and 2025. Selection was carried out through screening titles, abstracts, and full-text review according to inclusion and exclusion criteria. This resulted in 20 relevant articles for descriptive and systematic analysis. Results: Proper use of PPE, good personal hygiene, and controlling exposure to irritants were the most consistent factors in preventing DKAK. Conclusion: Prevention of occupational contact dermatitis requires an integrated and sustainable approach involving exposure control, education, use of PPE, and improvements to the work environment. Keywords: Contact Dermatitis; Occupational Contact Dermatitis; Prevention; Risk Factors; Systematic Literature Review. Pendahuluan: Dermatitis kontak akibat kerja (DKAK) merupakan masalah kesehatan kerja yang signifikan, terutama pada pekerja industri yang rutin terpapar bahan kimia dan iritan. Faktor risiko bersifat multifaktorial, meliputi faktor pekerjaan (lama dan frekuensi kontak bahan kimia, wet work), faktor individu (usia, jenis kelamin, riwayat atopi, personal hygiene), serta faktor lingkungan kerja (suhu, kelembapan, ketersediaan sarana sanitasi, dan penggunaan APD). Pencegahan efektif meliputi pengendalian paparan, penggunaan APD yang tepat, edukasi dan pelatihan pekerja, serta perbaikan lingkungan kerja untuk menjaga integritas kulit dan menurunkan insiden DKAK. Tujuan: Untuk mengetahauhi faktor resiko dan pencegahan dermatitis kontak akibat kerja. Metode: Penelitian ini menggunakan metode systematic literature review dengan penelusuran literatur melalui PubMed, ScienceDirect, Scopus, Google Scholar, dan ProQuest terhadap artikel yang diterbitkan pada periode 2020–2025. Seleksi dilakukan melalui screening judul, abstrak, dan telaah teks lengkap sesuai kriteria inklusi dan eksklusi, sehingga diperoleh 20 artikel relevan yang dianalisis secara deskriptif dan sistematis. Hasil: Penggunaan APD yang tepat, personal hygiene yang baik, serta pengendalian paparan bahan iritan merupakan faktor yang paling konsisten berperan dalam pencegahan DKAK. Simpulan: Pencegahan dermatitis kontak akibat kerja memerlukan pendekatan terpadu dan berkelanjutan yang melibatkan pengendalian paparan, edukasi, penggunaan APD, dan perbaikan lingkungan kerja. Kata Kunci: Dermatitis Kontak; Faktor Risiko; Occupational Contact Dermatitis; Pencegahan; Systematic Literature Review.